(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2025)
Introduction. In today’s globalized environment, sales policy is a key factor in the success of companies in international markets. At the same time, ethical principles are becoming an important component that maintains consumer confidence and builds a positive brand image. Taking ethics into account in sales policy contributes to sustainable business development, avoidance of conflicts and formation of a responsible corporate culture. Therefore, the study of this issue is of great practical and theoretical importance The purpose of the article. The purpose of the article is to study the peculiarities of forming and implementing a sales policy in international activities with due regard for ethical principles, to determine the impact of business ethics on sales policy, and to propose recommendations for integrating ethical principles into the sales policy of an enterprise. Methods. To study sales policy in international activities, taking into account ethical principles, a set of methods was used, including analysis of scientific literature to study theoretical foundations, comparative analysis of international companies’ practices, and interpretation of the results obtained to formulate conclusions and recommendations. Results. It has been found that the formation of an effective sales policy in the international activities of enterprises is one of the key factors in ensuring their competitiveness in global markets. That is why it is important to study this policy in the context of compliance with ethical standards and principles that must be integrated into all components of the sales process. Sales policy in international activities is defined as a set of measures, strategies, and tools aimed at ensuring the effective movement of products from the manufacturer to the end consumer outside the country of origin. It is outlined that business ethics in an international environment acts as a system of moral norms and standards, compliance with which ensures honest conduct of economic activities and prevents discrimination, fraud, or other forms of dishonest behavior. Key ethical principles that are determined when forming a sales policy are classified. The practice of leading international corporations has been studied, which shows that the integration of ethical norms into sales policy is gradually becoming not a recommendation but a requirement of the modern market. Ethical principles in sales policy play a key role in building consumer trust, enhancing the company’s reputation, and ensuring sustainable business development at the international level. The study proposes recommendations for effectively integrating ethical principles into the sales policy of enterprises. The implementation of these measures will contribute to building trust in the brand, reducing the risk of legal conflicts, and increasing the effectiveness of the sales policy of enterprises in international markets. The study also examines Ukrainian businesses facing unprecedented challenges, where the implementation of ethical principles in sales policy contributes to the formation of a corporate culture of responsibility, which is the foundation for the recovery and development of the country’s economy in the post-war period. Conclusiоns. Sales policy in international activities has a significant impact on the success of companies in global markets, and taking into account ethical principles is a prerequisite for building consumer and partner trust. Business ethics helps to avoid conflicts, enhances brand image and contributes to the sustainable development of enterprises. The analysis of practices has shown that the integration of ethical standards into sales policy increases its effectiveness and social responsibility of companies. Implementation of ethical standards contributes to the development of corporate culture and long-term competitiveness of Ukrainian companies in the international arena.